Kolaborasi Guru Bimbingan dan Konseling dengan Pihak Sekolah dalam Menangani Siswa Bolos di MAN 1 Kota Payakumbuh - Mia Junita; Yeni Afrida (YASIN, 2026)
Truancy remains a disciplinary problem in schools that may hinder students’ academic and social development. Although collaboration in guidance and counseling services has been widely studied, research specifically examining patterns of collaboration between guidance and counseling (BK) teachers and various school personnel in addressing student truancy remains limited. This study aimed to analyse the collaboration of BK teachers with homeroom teachers, subject teachers, and the vice principal for student affairs in addressing student truancy at MAN 1 Kota Payakumbuh. This study employed a qualitative approach with a case study design and involved four informants selected using purposive sampling. Data were collected through interviews, observations, and documentation and were subsequently analysed using the interactive model of Miles, Huberman, and Saldaña, which comprises data reduction, data presentation, and conclusion drawing. The results showed that student truancy was addressed through systematic collaboration among BK teachers, homeroom teachers, subject teachers, and the vice principal for student affairs. This collaboration was implemented through case identification, information exchange, student guidance, parental summons, the application of a violation point system, and the monitoring of student progress. This study confirms that coordination among school personnel is an important element in supporting the effectiveness of truancy management. These findings contribute to the development of BK services based on collaborative guidance and counseling and broaden the understanding of the importance of cooperation among school personnel in addressing student disciplinary problems. The practical implications of this study may serve as a reference for schools in strengthening collaborative systems in BK services and as a basis for future research to develop a more comprehensive collaboration model.